Dowry Prohibition Laws in Bangladesh: Problems of Implementation - Taher, Mohammad Abu; Jamaluddin, Siti Zaharah (Journal of Malaysian and Comparative Law, 2014)
The practice of dowry, which is neither supported by personal law nor State laws, has become an acute problem resulting in breakage of social malady and texture in Bangladesh in recent years. The dangerous aspect relating to it is the physical and mental torture on the wife due to inadequate or non-payment of dowry. Every year a number of women are tortured, killed and considerable numbers of women commit suicide for this existing evil custom. To deal with this social menace, the Parliament of Bangladesh enacted the Dowry Prohibition Act, 1980, which was subsequently amended in 1982, 1984 and 1986. In 2000, a more stringent law i.e. the ‘Women and Children (Repression Prevention) Act, 2000’ was passed by the Parliament to prevent cruelty against women including dowry-related violence. This Act was amended in 2003 to remove certain loopholes and to make it more severe. But all the efforts of the government ended in vain, as a good number of instances are being reported regarding torture and oppression of women every now and then due to dowry. Although specific laws have been formulated to deal with these matters, these laws are not effectively implemented to eradicate the practice of dowry from the society and to stop the violence against women relating to dowry due to various problems. Thus, based on detailed fieldwork, this paper is an attempt to identify the problems that hinder the effective enforcement of the dowry prohibition laws in Bangladesh.